2001
DOI: 10.1146/annurev.anthro.30.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality, Culture, and Power in HIV/AIDS Research

Abstract: ▪ Abstract  This article examines the development of anthropological research in response to AIDS. During the first decade of the epidemic, most social science research focused on the behavioral correlates of HIV infection among individuals and failed to examine broader social and cultural factors. By the late 1980s, however, pioneering work by anthropologists began to raise the importance of cultural systems in shaping sexual practices relevant to HIV transmission and prevention. Since the start of the 1990s,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(141 citation statements)
references
References 89 publications
1
133
0
7
Order By: Relevance
“…In Karnataka specifically, a large number of women enter sex work through a religious tradition called the Devadasi (O'Neil et al, 2004). These cultural factors present unique challenges to HIV prevention efforts and are further influenced by wider social and sexual inequalities that shape the experience of HIV/AIDS risk reduction strategies (Parker, 2001). Sex worker communities are subjected to severe forms of stigma, discrimination and violence and as a result face formidable barriers to accessing services.…”
Section: Structural Interventions and The Impact On Personal Riskmentioning
confidence: 99%
“…In Karnataka specifically, a large number of women enter sex work through a religious tradition called the Devadasi (O'Neil et al, 2004). These cultural factors present unique challenges to HIV prevention efforts and are further influenced by wider social and sexual inequalities that shape the experience of HIV/AIDS risk reduction strategies (Parker, 2001). Sex worker communities are subjected to severe forms of stigma, discrimination and violence and as a result face formidable barriers to accessing services.…”
Section: Structural Interventions and The Impact On Personal Riskmentioning
confidence: 99%
“…Different actors within institutions construct social meanings about whether sexual activity is permitted or not, who it is permitted for, for what outcomes, how and when to become sexually active (WIGHT et al, 2012;PARKER, 2001). In turn, these social meanings are internalized by individuals and groups, including adolescents, and may influence the way they perceive their own sexuality, as well as the way they engage in actual sexual behaviours, access and use of available health information and services on the same issue.…”
Section: Setting the Fieldmentioning
confidence: 99%
“…A minimum standard for international research is necessary for scientific and ethical reasons. It has been suggested that those researching cultures foreign to them must immerse themselves in the culture, must be familiar with the formal and colloquial use of the native language, and must examine the sociocultural factors that influence behavior in that culture (Parker, 2001;Rebhun, 1999).…”
Section: Actively Involve Researchers and Partners;mentioning
confidence: 99%